2019
DOI: 10.1159/000500523
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Circulating Levels of Asprosin in Obese Children

Abstract: Background: Circulating asprosin is a newly discovered adipokine that triggers the release of hepatic glucose stores and increases appetite. Asprosin levels are elevated in adult obese men as well as in mice, and reductions in asprosin protect against the hyperinsulinism associated with metabolic syndrome in mice with diet-induced obesity, which indicates a potential therapeutic role of asprosin in obesity and type 2 diabetes. Objectives: Few data on asprosin in children are available, which is why this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 18 publications
5
69
3
Order By: Relevance
“…In our study, we found that serum asprosin levels were significantly higher in obese children compared with normal weight controls. As previously reported by Long et al we found a gender difference in terms of asprosin levels . We also compared serum asprosin and other variables between boys and girls and found that there was no difference in terms of serum asprosin levels.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In our study, we found that serum asprosin levels were significantly higher in obese children compared with normal weight controls. As previously reported by Long et al we found a gender difference in terms of asprosin levels . We also compared serum asprosin and other variables between boys and girls and found that there was no difference in terms of serum asprosin levels.…”
Section: Discussionsupporting
confidence: 76%
“…They also reported that asprosin was correlated with BMI, HOMA‐IR, insulin, and HDL after adjusting for age in boys. They concluded that there was a gender difference in terms of serum asprosin levels . In our study, we found that serum asprosin levels were significantly higher in obese children compared with normal weight controls.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Another cross-sectional study showed that serum asprosin concentrations markedly decreased in obese 6-to 14-year-old children compared to healthy normal-weight children. Asprosin was negatively associated with BMI if adjusted for age and sex, which is not consistent with the results of the previously mentioned studies; this indicates the complex role of asprosin in obesity (27).…”
Section: Asprosin In Obesitycontrasting
confidence: 83%
“…The olfactory receptor OLFR734 specifically binds with asprosin to modulate hepatic glucose production [8]. Several recent studies have shown that asprosin correlated with obesity in children and adults, T2DM and PCOS [9][10][11][12][13][14][15][16].…”
Section: / 16mentioning
confidence: 99%